PENGARUH PEMANFAATAN ABU SEKAM PADI PADA BATA BETON RINGAN FOAM TERHADAP KUAT TEKAN, BERAT JENIS, DAN DAYA SERAP AIR SEBAGAI SUPLEMEN BAHAN AJAR MATA KULIAH TEKNOLOGI BETON (PADA MAHASISWA SEMESTER III PTB FKIP UNS) - Ari Sri Wahyuni; Chundakus Habsya; Ernawati Sri Sunarsih (Indonesian Journal Of Civil Engineering Education, 2015)
The purposes of this research were to viralslot, (1) determine the influence of rice husk ash as smooth aggregate partial substitute and foam variation towards compressive strength, density, and absorption of lightweight foam concrete brick, (2) determine the percentage of rice husk ash as smooth aggregate partial substitute and foam variation to achieve the compressive strength which fulfilled SNI No. 03 – 0349 – 1989, (3) determine the percentage of rice husk ash as smooth aggregate partial substitute and foam variation to achieve the density lightweight concrete which fulfilled SNI No. 03 – 0349 – 1989, (4) determine the percentage of rice husk ash as smooth aggregate partial substitute and foam variation to achieve the absorption which fulfilled SNI No. 03 – 0349 – 1989, (5) produce course material supplement of concrete technology on the influence of using rice husk ash in lightweight foam concrete brick toward compressive strength, density, and absorption. This research used experimental method and data analysis techniques used regression analysis. Variables in the study were (1) dependent variables: compressive strength, density, and absorption of lightweight foam concrete bricks, (2) independent variables: the substitute of smooth aggregate to rice husk ash with variation 0%, 25%, 35%, and 45% and foam variation 0,2 and 0,3 of concrete volume.Based on the results of the study concluded that, (1) variation of rice husk ash and foam was strongly influence towards the compressive strength, density, and absorption of lightweight foam concrete bricks, (2) There was no percentage of rice husk ash and foam to achieve the compressive strength of lightweight foam concrete brick which fulfilled SNI No. 03 – 0349 – 1989, (3) All percentages of rice husk ash and foam variation produced the density value of lightweight foam concrete brick which fulfilled SNI No. 03 – 0349 – 1989, (4) All percentages of rice husk ash and foam variation produced the absorption value of lightweight foam concrete brick which fulfilled SNI No. 03 – 0349 – 1989, (5) the output course materials was a course materials supplement about the influence of the use rice husk ash as partly smooth agregate substitute of lightweight foam concrete brick to compressive strength, density, and absorption.Keywords: rice husk ash, foam, lightweight foam concrete bricks viralslot .